2018
DOI: 10.9755/ejfa.2018.v30.i3.1638
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on in situ ruminal degradability of grains and meals for energy concentrate feeds

Abstract: One factor that may interfere with rumen fermentation is the physical form of feed, because of the colonization by bacteria during processing. Here, we aimed to perform a meta-analysis and evaluate the in situ ruminal degradability of energy feeds with distinct physical forms (grain vs. meal). We created a database, comprising 39 treatments from 12 studies conducted in Brazil, and focused on parameters for the potential and effective degradability of dry matter (DM) and crude protein (CP) of energy feeds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, this study concluded that, quantitatively, the decrease was only found in EE and DM. Different results were obtained byBusanello et al (2018) through a metaanalysis study that there is no effect of DM from physical processing on the nutrient content of feed ingredients. The DM loss in large quantities will have a negative impact on the nutrient content in available for absorption by ruminants.…”
mentioning
confidence: 94%
“…However, this study concluded that, quantitatively, the decrease was only found in EE and DM. Different results were obtained byBusanello et al (2018) through a metaanalysis study that there is no effect of DM from physical processing on the nutrient content of feed ingredients. The DM loss in large quantities will have a negative impact on the nutrient content in available for absorption by ruminants.…”
mentioning
confidence: 94%
“…Ingredients that present protein from natural sources are usually expensive, but the inclusion of nitrogen compounds of non-protein origin in the diet makes it possible to reduce production costs, since it has a lower price per unit of protein equivalent. Therefore, the use of these ingredients that promote a greater release of ammonia in the rumen allows the optimization of the nitrogen use, increasing the consumption, due to the improvement in the ruminal fermentation; thus, maximizes ruminal metabolism; which will consequently benefit animal performance (Seo et al 2010;Busanello et al 2018). Corn (carbohydrate) is used as a starch source, being the main energy component of the concentrates.…”
Section: Introductionmentioning
confidence: 99%